Computer mathematics : proceedings of the fifth Asian Symposium (ASCM 2001), Matsuyama, Japan, 26-28 September 2001 - Shirayanagi, Kiyoshi; Yokoyama, Kazuhiro (Lecture notes series on computing ;, 2001)
This volume covers some of the most recent and significant advances in computer mathematics, including algebraic, symbolic, numeric and geometric computation, automated mathematical reasoning, mathematical software and computer-aided geometric design. Researchers, engineers, academics and graduate students interested in doing mathematics using computers will find this volume good reading and a valuable reference.